2023
DOI: 10.1021/acsami.3c11961
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Ignition and Combustion Performances of Solid Propellants Incorporating Al Particles Inside Oxidizers

Ruixuan Xu,
Minghui Yu,
Zhihua Xue
et al.

Abstract: The combustion efficiency of Al plays a critical role in the combustion of high-energy aluminum-based solid propellants. For traditional formulations, the Al powders are dispersed in the binder matrix, leading to limited contact with the oxidizers and hence usually insufficient combustion and higher values of the pressure exponent. In this paper, various core–shell structural Al/oxidizer composites such as Al@HMX, Al@AP, and AP@Al have been prepared by a spray-drying technique based on which solid propellants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…It can be seen that Al and catalyst are uniformly distributed in composite particles and the Al particles are fully covered with CL-20. This structure, where Al particles are isolated in small cells composed of CL-20, can improve the uniformity of the composites and facilitate more effective reaction between Al particles and the gaseous products of CL-20, thereby greatly inhibiting the accumulation and aggregation of Al particles 22 and improving combustion efficiency of SCCs. For other SCCs, the distribution of each additive is similar (see it in Figure S2) to that of the composites shown in Figure 2, which means the concentration of GO-CHZ-Co has minor impact on the morphology and microstructure of the composites.…”
Section: Morphology Of Cl-20 and Sccsmentioning
confidence: 99%
“…It can be seen that Al and catalyst are uniformly distributed in composite particles and the Al particles are fully covered with CL-20. This structure, where Al particles are isolated in small cells composed of CL-20, can improve the uniformity of the composites and facilitate more effective reaction between Al particles and the gaseous products of CL-20, thereby greatly inhibiting the accumulation and aggregation of Al particles 22 and improving combustion efficiency of SCCs. For other SCCs, the distribution of each additive is similar (see it in Figure S2) to that of the composites shown in Figure 2, which means the concentration of GO-CHZ-Co has minor impact on the morphology and microstructure of the composites.…”
Section: Morphology Of Cl-20 and Sccsmentioning
confidence: 99%
“…In the meantime, the agglomeration of molten Al particles has been effectively inhibited. Other studies have shown that the catalyzed Al@HMX composite material enhanced the heat of reaction by 9.8% and reduced ignition delay by 55 ms compared to that of the mechanical mixture. , For Al@HMX-containing propellants, the value of n decreased to 0.19 within the pressure range of 1–15 MPa, indicating an improved ignition and combustion performance was achieved. With other oxidizers to be integrated, the Al@AP propellants precisely catalyzed with CuO have been found to greatly suppress n from 0.42 to 0.21 .…”
Section: Introductionmentioning
confidence: 99%